Study on the p Bond of Small Organic Molecules and Hydrogen Halide Interaction - Yang, Jie; Li, Shaobo; Yang, Benhong; Shao, Guoquan (Asian Journal of Chemistry, 2012)
We applied ab initio theoretical studies on the complex of C2H4 and HX, formed by X-H···p, respectively. First, the monomers and complex were optimized at the MP2/cc-pVTZ level. Then, we regulated the BSSE and calculated the binding energy of different systems at the same level with the correction of BSSE by using counterpoise method at the MP2/aug-cc-pVTZ level. The results demonstrated that C2H4···HX (X = F, Cl, Br, I), with increasing halogen atomic number,from HF to HI, the bond length have all increasing, however, the binding energy of complex present in the overall decreasing trend.